Специфіка переосмислення шекспірівського сюжетно-образного матеріалу у повісті І.Тургенєва „Гамлет Щигровського повіту” - Василина, К. (Інститут літератури ім. Т.Г.Шевченка НАН України, 2009)
В статье представлен сравнительный анализ повести И.Тургенева и трагедии В.Шекспира, нацеленный на выявление специфики рецепции шекспировского наследия в русской литературе XIX в. Делается вывод о том, что в процессе интерпретации шекспировского образа и сюжета И.Тургенев прибегает к таким способам трансформации традиционного материала, как модернизация, национализация, техника «сюжета в сюжете», семантическое переакцентирование образа и др. Предлагая собственную интерпретацию концепта русского гамлетизма, автор повести выражает свое отношение к политическим и экономическим реформам тех лет. The article is devoted to comparative analysis of the short novel by Turgenev and the tragedy by Shakespeare with the aim of defining the ways and means of Shakespearean heritage perception in Russian literature of the 19th C. It is stressed that while interpreting Shakespearean image and plot Ivan Turgenev uses such means of transforming the traditional material as modernization, nationalization, “plot inside the plot” techniques, semantic expansion of the image etc. Offering his own interpretation of the Russian Hamletism concept the author of the short novel presents his vision of political and economic reforms of the day.